Triboelectric Nanogenerators: Contribution of Ferromagnetic Medium to the Output of Triboelectric Nanogenerators Derived from Maxwell's Equations (Adv. Energy Mater. 21/2021). Issue 21 (2nd June 2021) - Li, Yahui; Li, Guizhong; Zhang, Penglei; Zhang, Haodong; Ren, Chao; Shi, Xian; Cai, Han; Zhang, Yanxin; Wang, Yusen; Guo, Zhanfeng; Li, Hongfang; Ding, Guifu; et al.
Abstract : In article number 2003921, Zhuoqing Yang, Chi Zhang, Zhong Lin Wang and co‐workers theoretically and experimentally verify the output characteristics of triboelectric nanogenerators (TENGs) based on Maxwell's equations, which include both polarization and magnetization effects. For the first time, the discovered output characteristics of TENGs are precisely derived from the working principle of TENGs, simultaneously, a completed and unified theoretical system is constructed for TENGs.